2018
DOI: 10.1016/j.anifeedsci.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the accuracy of current near infra-red reflectance spectroscopy analysis for fresh grass-clover mixture silages and development of new equations for this purpose

Abstract: Assessing the accuracy of current near infrared reflectance spectroscopy analysis for fresh grassclover mixture silages and development of new equations for this purpose. Animal Feed Science and Technology, 239. pp. 94106.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The UoR experiment involved a total of thirty-six wether Texel x Mule sheep in an in vivo digestibility study that has been described previously. 30 In brief, ninety perennial ryegrass (PRG) and clover mixture silages with a range of clover concentrations from 40 to 1000 g/kg DM were each fed to three sheep in multiple 3x3 Latin Square designs with five day diet and faecal collection periods for determination of digestibility. Silages were obtained as large bales or chopped clamp material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UoR experiment involved a total of thirty-six wether Texel x Mule sheep in an in vivo digestibility study that has been described previously. 30 In brief, ninety perennial ryegrass (PRG) and clover mixture silages with a range of clover concentrations from 40 to 1000 g/kg DM were each fed to three sheep in multiple 3x3 Latin Square designs with five day diet and faecal collection periods for determination of digestibility. Silages were obtained as large bales or chopped clamp material.…”
Section: Methodsmentioning
confidence: 99%
“…Diet and fecal samples for calibration development were obtained from two sheep feeding trials, the first at the University of Reading (UoR), U.K., and the second at the Agri-Food and Biosciences Institute for Northern Ireland (AFBI), U.K.. The UoR experiment involved a total of 36 wether Texel x Mule sheep in an in vivo digestibility study that has been described previously . In brief, 90 perennial ryegrass (PRG) and clover mixture silages with a range of clover concentrations from 40 to 1000 g/kg DM were each fed to three sheep in multiple 3 × 3 Latin Square designs with 5 day diet and fecal collection periods for determination of digestibility.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, breakthroughs have been made with regard to NIRS analyses of fresh forage and grass using conventional NIR instruments. Thomson et al [80] investigated if a pre-existing fresh grass silage NIRS calibration could predict quality in grass/clover silage samples in the UK. The study found that some parameters such as DMD could be predicted with acceptable accuracy.…”
Section: Grass Quality Analysis By Means Of Near Infrared Spectroscopymentioning
confidence: 99%
“…Currently, the NIRS literature consists of hundreds of research articles related to forage near infrared (NIR) analysis. In the beginning these papers were done using dried and finely milled samples (Coelho et al, 1988;Decruyenaere et al, 2009), but later the research was extended to cover wet forages (Park et al, 1998;Sørensen, 2004;Thomson et al, 2018). However, in comparison, the NIRS scientific literature related to TMR is rather limited.…”
Section: Introductionmentioning
confidence: 99%